The Long-Run Effects of Monetary Policy - Jordà, Òscar; Singh, Sanjay R.; Taylor, Alan M. (The Review of Economics and Statistics, 2024)
Abstract We document that the real effects of monetary shocks last for over a decade. Our approach relies on (1) identification of exogenous and non-systematic monetary shocks using the trilemma of international finance; (2) merged data from two new international historical cross-country databases; and (3) econometric methods robust to long-horizon inconsistent estimates. Notably, the capital stock and total factor productivity (TFP) exhibit greater hysteresis than labor. When we allow for asymmetry, we find these effects with tightening shocks, but not with loosening shocks. When extending the horizon of the responses reported in several recent studies that use alternative monetary shocks, we find similarly persistent real effects, thus supporting our main findings.